Treatment of hypothyroidism using Korean medicine: 2 case reports. Issue 18 (May 2020) - Kim, Hyongjun; Moon, Sun-Young; Han, Kyungsun; Lee, Jun-Hwan; Im, Jong Hwan; Kim, Sungha; Yoo, Jeong-Eun
Abstract: Introduction: Hypothyroidism, the most common endocrine disease, comprises a deficiency of thyroid hormone, causing coldness, fatigue, and dysmenorrhea. Here, we report the improvement of hypothyroidism symptoms and thyroid hormone level normalization by using Korean herbal medicine and acupuncture therapy. Patient concerns: A 30-year-old woman (Case 1) presented at the clinic with continuous seborrheic dermatitis on the scalp, accompanied by dysmenorrhea. A 55-year-old woman (Case 2) presented with symptoms of coldness of the limbs and fatigue. Diagnosis: Both patients were diagnosed with "Yin deficiency and Yang hyperactivity" and hypothyroidism after serum thyroid function tests. Interventions: Both patients received herbal medicine decoction, acupuncture, and electroacupuncture therapy. Outcomes: Korean medicine improved the symptoms of hypothyroidism and significantly normalized thyroid-stimulating hormone and free-thyroxine levels. Conclusion: These outcomes suggest that Korean medicine may be effective for resolution of hypothyroidism; however, further research is needed to confirm these findings.